An investigation on vibration features of a gear-bearing system involved pitting faults considering effect of eccentricity and friction. (January 2022) - Zhao, Wei-qiang; Liu, Jie; Zhao, Wen-hui; Zheng, Yang
Highlights: A dynamic model of gear-rotor-bearing with pitting faults considering friction and eccentricity is proposed. The vibration features of the gear system with different pitting area ratios are firstly investigated. The increase of eccentricity greatly influences the rotational frequency and cause low frequency and significant amplitude condition. The change of friction coefficient can affect the degree of meshing impact in the pitting area. Abstract: In this paper, a dynamics model of a bending-torsion coupled gear-bearing transmission system is developed, and the vibration features of a pitting fault gear system considering eccentricity and friction are analyzed. Firstly, the time-varying meshing stiffness of pitting faulty propagation is calculated by the parsing method. The vibrational differential equations for this model are obtained using an energy approach based on Lagrange equations. Then, the equations are solved using the Runge-Kutta method to obtain the vibration response of the system. Finally, the effect of the pitting area ratio on the vibration features of the pitting faulty gear is analyzed by the time, frequency, and time–frequency domains. The sideband rating factor is presented to evaluate the influences of pitting faults. The effects of the eccentricity and friction on the impact caused by the pitting is analyzed.